Economic analysis of radiological examinations in healthcare: balancing government expenditures and patient burden - Khamidov Obid Abdurakhmanovich; Umarov Far rux Umarovich (THE INNOVATION ECONOMY, 2026)
Radiological examinations are one of the most crucial stages in the process of detecting, monitoring, and treating diseases in the healthcare system. This article explores various types of radiological diagnostics, their cost-ef fectiveness, and the balance between state budget expenditures and patient costs. Existing practices in Uzbekistan’s healthcare system are compared with international experience and analyzed using cost-benefit analysis (CBA) and health technology assessment (HTA) methods. The economic efficiency of X-ray techniques is evaluated based on statistics, charts, and tables